Structural Social Capital Studies in Management and Organization Literature: A Bibliometric Network Study - Alan Hale; Köker Ali Riza (Central European Management Journal, 2021)
Purpose: Many empirical and review studies have been performed in the management and organization literature from the structural social capital perspective. Since these studies focus on different topics periodically, we aimed to make a bibliometric analysis of the structural social capital literature that allows a regular, systematic, and quantitative evaluation of published articles in management and organization science to identify the underlying structure in this research area and to identify the main research themes of the scholarship.